Polskie zainteresowania Afryką Północną do początku XX w. - Jacek Knopek (Świat Idei i Polityki, 2001)
It must be stated that North Africa was best known in the Polish land up to the beginning of the 20,h c. Polish individual social classes, similarly to other middle European communities, had different imaginations about the Dark Continent. It is admitted that the more educated and wealthy social class, the better this part of the world was known. Amongst the countries of North Africa, Egypt was the one the knowledge of which reached Poland most often and enjoyed much interest. It could happen due to the fact that Egypt was on the way of Polish peregrinations and travels to the countries of the Middle East and Holy Land. The Poles going to the east side of the Mediterranean Sea also visited this country of pyramids. Knowledge about the other countries of North Africa began to reach Poland at the end of the 18,h century due to frequent Polish travels to that part of the world. However, our knowledge of the land starts only with the thirties of the 19'h century, i.e. when North-West Africa began to be colonized by France and Spain, and when Great Britain started to be interested in Egypt.